(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
The endophytic fungi isolated from different plant parts including leaf, stem and rhizome of Curcuma mangga were screened for antimicrobial activity by employing agar plug diffusion assay and disc diffusion assay for primary screening and secondary screening, respectively. A total of 127 endophytic fungi that were successfully isolated from various plant parts were cultured to examine their antimicrobial activities. Qualitative screening using agar plug diffusion assay revealed that 118 isolates (92.9%) showed antimicrobial activity against at least on one test microorganisms and suggested that the rhizome part exhibited the highest percentage of antiyeast (58.3%) and antifungal (91.7%) activities compared to leaf and stem parts. Quantitative screening using disc diffusion assay indicated that ethyl acetate extract from fermentative broth (extracellular compound) demonstrated better antimicrobial activity compared to methanol extract derived from fungal biomass (intracellular compound) against all the four classes of pathogenic microorganisms tested (Gram-positive bacteria, Gram-negative bacteria, yeast and fungi). The future of endophytic fungus study is very promising as it possesses hidden potential to be developed as natural antimicrobial agent.